(3GdOQI GdjJjeI hGdMLI GdeSJbjeIs - (3jMji Hf jhSa Hf jMji Hf efUhQ Hf GdeYeQ Hf YHO GdYRjR GdUQUQj, LeGd GdOjf CHh eMeO,J (B656 (3g` s ((3eMeO Hf Ydi GdMfHdi s)
(3ChdgG (B:s
(3CeG HYO aEfi fXeJ HfjI UGdMI hWhjI fGUMI dG Ybd CegGJ eSGFd Gdabg Ydi fGTOgG s
(3BNQgG (B:s
(3HGH YJb CegGJ GdChdGO s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B177s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJjI GdOhdI (B- (3HQdjf (B- (3GdeGfjG GdZQHjI (B(4511) s
Keywords: (3Gdabg GdMfHdjs